Synthesis of Silver(I) Complexes Containing N and P Donor Ligands - Sarath D. Perera (The Open University of Sri Lanka, 2021)
Treatment of one equivalent of 3,4,5,6-tetraphenyl-2,2'-bipyridine (tpbpy) with AgClO4 afforded [Ag(tpbpy)]ClO4 (1a). Similarly, [Ag(tpbpy)]BF4 (1b) was prepared using AgBF4. Reaction of two equivalents of tpbpy with AgClO4 yielded the homoleptic Ag(I) complex [Ag(tpbpy)2]ClO4 (2). The four-coordinate heteroleptic Ag(I) complex [Ag(tpbpy)(xantphos)]ClO4 (3) containing both N and P donor ligands was prepared by treating AgClO4 with a (1:1) mixture of tpbpy and 4,5-bis(diphenylphosphino)-9,9'-dimethylxanthene (xantphos). [Ag(dmbpy)(xantphos)]ClO4 (4) (dmbpy = 6,6'-dimethyl2,2'-bipyridine) was prepared in a similar manner. Reaction of one equivalent of xantphos with AgClO4 in acetonitrile produced the labile three-coordinate Ag(I) complex [Ag(xantphos)(MeCN)]ClO4 (5). Treatment of (5) with one equivalent of tpbpy or dmbpy afforded the heteroleptic complexes (3) and (4), respectively. Reaction of (5) with one equivalent of 4'-(4-methylphenyl)-2,2':6',2''-terpyridine (ttpy) afforded the five-coordinate Ag(I) complex [Ag(xantphos)(ttpy)]ClO4 (6). Treatment of AgClO4 with one equivalent of bis(diphenylphosphino)methane (dppm) in a (1:1) solvent mixture of chloroform and methanol resulted in the formation of [Ag2(μ-dppm)2][ClO4]2 (7). Reaction of (7) with one equivalent of 3,6-di(2-pyridyl)-4,5-diphenyl-pyridazine (dppz) gave the binuclear complex [Ag2(μ-dppm)2{μ-dppz}][ClO4]2 (8). Above complexes were characterized by a combination of elemental analysis, IR, Mass and NMR spectroscopy